Real Sister : Stereotypes, Respectability, and Black Women in Reality TV - Ward, Jervette R., 1983- (Book collections on Project MUSE., 2015)
From The Real Housewives of Atlanta to Flavor of Love , reality shows with predominantly black casts have often been criticized for their negative representation of African American women as loud, angry, and violent. Real Sister brings together ten black female scholars from a variety of disciplines, in part to address legitimate concerns about how reality TV reinforces stereotypes, but also to inspire a more nuanced conversation about the genre's representations and their effects on the black community.